Refined assessment of potential evapotranspiration in the tarim basin - Huo, Wen; Zhi, Xiefei; Hu, Shunqi; Cai, Wenyue; Yang, Fan; Zhou, Chenglong; MamtiMin, Ali; He, Qing; Pan, Honglin; Song, Meiqi; Wen, Cong; Wang, Yu; et al. (Frontiers in Earth Science, 2022)
As an important part of surface hydrothermal process, the study of evapotranspiration has been paid more attention, and it has an important reference value for the optimal allocation of regional water resources. It hinders the accurate assessment of evapotranspiration in arid zones and its response to climate change because human activities have changed the original underlying surface of deserts and increased the complexity of calculations. In this study, the encrypted observations of natural sand land（hereinafter referred to as NSL）and constructed green land（hereinafter referred to as CGL）in the heartland of the Taklimakan Desert were analyzed by the Penman-Monteith-H (PM-H) numerical model to accurately assess the applicability of the evapotranspiration calculation method to different underlying surfaces, analyze the associated errors, and quantify the effects and contributions of the main impacting meteorological factors on the evapotranspiration calculation. Our study finds that the PM-H algorithm exhibits good applicability in Tarim Basin, where the vegetation growth period significantly affects evapotranspiration. The evapotranspiration calculation is positively affected by the difference between saturated and actual vapor pressures and the 2-m mean wind speed and negatively affected by the 2-m mean temperature and gradient of saturated water pressure. Based on high-resolution grid data, the applicability of the PM-H algorithm has been improved, and our calculations show that the mean annual potential evapotranspiration in the Tarim Basin is 2750 mm.